POST-PANDEMIC MSMEs RECOVERY CHALLENGES AND STRATEGIES IN MEDAN CITY - Pangeran Pangeran (UNIVERSITAS PAKUAN, 2022)
The Covid 19 pandemic is a situation that has a very direct impact on MSMEs. The situation of spread of this disease greatly disrupts the activities of human life, including in the world of economy and trade. MSMEs as the basis of the people's economy at the grassroots level have been severely affected, starting from bans on leaving the house, restrictions on trading hours, to forced closures due to the implementation of the Community Activity Restrictions (PPKM) policy. The real impact is that sales figures fell drastically and prices of basic necessities rose sharply. This paper aims to analyze the challenges and strategies for MSME recovery in the city of Medan after the pandemic. To discuss this problem using the method of literature study. The results of the discussion show that MSMEs in Medan City are deemed necessary to take advantage of the role of digitalization technology in supporting smooth promotions and sales, establishing partnerships with financial sector institutions in terms of capital, and building partnerships with various organizations and business partners to expand business networks. Taking advantage of opportunities for assistance from Medan City Government programs such as participating in the E-Catalog program means that the Medan City Government becomes a market (buyer) and also an intermediary for MSMEs products in Medan City.